2012
DOI: 10.1159/000338335
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline-Induced Cardiotoxicity: Cardiac Monitoring by Continuous Wave-Doppler Ultrasound Cardiac Output Monitoring and Correlation to Echocardiography

Abstract: Background: Anthracyclines are agents with a wellknown cardiotoxicity. The study sought to evaluate the hemodynamic response to an anthracycline using realtime continuous-wave (CW)-Doppler ultrasound cardiac output monitoring (USCOM) and echocardiography in combination with serum biomarkers. Methods: 50 patients (26 male, 24 female, median age 59 years) suffering from various types of cancer received an anthracycline-based regimen. Patients’ responses were measured at different time points (T0 prior to infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This characteristic may help identify vulnerable populations with pre-existing subclinical disease in addition to patients sensitive to chemotherapy induced damage [87,103,104]. …”
Section: Discussionmentioning
confidence: 99%
“…This characteristic may help identify vulnerable populations with pre-existing subclinical disease in addition to patients sensitive to chemotherapy induced damage [87,103,104]. …”
Section: Discussionmentioning
confidence: 99%
“…Due to differences in conclusion, study design and importantly the majority of the studies are based on <50 patients it is difficult to draw definite conclusions [26][31].…”
Section: Discussionmentioning
confidence: 99%
“…Although they are normally undetectable, troponins may increase within 2 or 3 hours after cardiac damage occurs . Studies have shown that troponins may detect cardiotoxicity at a preclinical phase, long before any reduction in LVEF has occurred, in patients treated with antitumor drugs (Table ) . Measurement of troponins may provide additional information, including: Prediction of the severity of future LVD, because the peak value of troponin after chemotherapy is closely correlated to the extent of LVEF reduction; Stratification of cardiac risk after chemotherapy, which allows for the personalization of the intensity of postchemotherapy monitoring of cardiac function; Selection of patients more prone to develop cardiotoxicity, in whom a cardioprotective therapy can be considered; and Exclusion of most patients from prolonged cardiologic monitoring. …”
Section: Detection Of Cardiac Dysfunction and Evidence For Cardiotoximentioning
confidence: 99%